2015
DOI: 10.1136/jfprhc-2014-100968
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive health needs of female sex workers and opportunities for enhanced prevention of mother-to-child transmission efforts in sub-Saharan Africa

Abstract: FSW have varying reproductive goals and contraceptive usage. Efforts to improve coverage of comprehensive family planning - including efforts to increase HIV testing and engagement in treatment among FSW trying to conceive - are necessary for PMTCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 22 publications
0
22
1
Order By: Relevance
“…Our findings also show that one-third (33.2%) of FSWs reported using no FP method and took no FP method at their Sauti visit, including condoms. Self-reported consistent condom use (with all partners, paying and non-paying) (16.1%) was also lower than in studies conducted in the region: a Swaziland study reported 23.5% consistent condom use [8], a Democratic Republic of the Congo study reported 40.0% [9], and a Swaziland, Togo, and Burkina Faso study showed 17.0% [7]. We acknowledge that the differences may be a byproduct of the methodologies associated with measurement design in a research setting, compared to a service delivery setting.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Our findings also show that one-third (33.2%) of FSWs reported using no FP method and took no FP method at their Sauti visit, including condoms. Self-reported consistent condom use (with all partners, paying and non-paying) (16.1%) was also lower than in studies conducted in the region: a Swaziland study reported 23.5% consistent condom use [8], a Democratic Republic of the Congo study reported 40.0% [9], and a Swaziland, Togo, and Burkina Faso study showed 17.0% [7]. We acknowledge that the differences may be a byproduct of the methodologies associated with measurement design in a research setting, compared to a service delivery setting.…”
Section: Discussioncontrasting
confidence: 54%
“…The study also revealed a complex pattern of paternity, with 36% of pregnancies among FSW being attributed to non-paying partners such as husbands or boyfriends, 23% to regular clients and 28% to casual clients [26]. In Togo, Burkina Faso, and Swaziland, 19% of FSWs in the study reported that they were trying to conceive [7]. The complexities of decision-making around FP choices and fertility intentions were beyond the scope of the study.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In a further analysis of the data from Burkina Faso and Togo, as well as data from Swaziland, FSWs who were living with HIV but had been previously undiagnosed were more likely to be trying to conceive compared to those who were HIV‐negative (Schwartz, Papworth, Ky‐Zerbo, et al. ). These findings further support the need for safer conception services to minimize HIV acquisition or transmission among members of key populations who are trying to conceive.…”
Section: Pregnancy Intentionsmentioning
confidence: 99%
“…7 Characterization of the needs of these women is important, given their unique occupational risks, fertility-related concerns, child-care needs and potential barriers to accessing support services and health care emanating from social stigma and discrimination. 8,9 …”
Section: Introductionmentioning
confidence: 99%